Abstraction networks: adapting abstraction hierarchies to map important relationships for system design. Issue 1 (March 2023) - Tewani, Priyanka; Jefferies, Christine M.; Reynolds, Morgan; Segarra, Gabriel; Rayo, Michael F.; Catchpole, Ken
Abstraction hierarchies (AHs) are essential to a work domain analysis (WDA), the "most important and unique" phase of cognitive work analysis (CWA) (Vicente, 1999). Although AHs have been the industry standard for assessing and describing work systems for several decades, they are not without limitations (Vicente, 2002). We have developed an evolution of AHs called Abstraction Networks (ANs) to address several of the limitations Vicente identified. ANs are designed to (1) improve engagement with practitioners, thereby facilitating greater shared understanding of the system, (2) better integrate with existing systems analysis tools, and (3) provide a more direct bridge between systems analysis and display design. We document a case study that uses ANs to better understand a sterile processing department (SPD) at a Southeastern tertiary care hospital, detailing the extent to which AN's achieve these three goals.